Transcriptome Analysis Revealed the Molecular Mechanism of Acetic Acid Increasing Monascus Pigment Production in Monascus ruber CICC41233 - Yan Wang; Weiwei Wu; Xiaoshu Wu; Weiyu Li; Jingjing Cui; Chuannan Long (Journal of Fungi)
The addition of acetic acid to Monascus ruber cultures is usually used to inhibit the growth of heterotrophic bacteria; however, we found that acetic acid also promotes the growth of M. ruber CICC41233, as well as the synthesis of Monascus pigments (MPs). Compared with no acetic acid or HCl addition, the diameter of M. ruber CICC41233 colonies increased significantly under acetic acid conditions. On the sixth day of fermentation, the yield of total pigments in M. ruber increased significantly by 9.97 times (compared with no acetic acid) and 13.9 times (compared with hydrochloric acid). The transcriptomics data showed that the differentially expressed genes between M. ruber with acetic acid and without acetic acid were mainly involved in starch and sucrose metabolism, glycolysis/gluconeogenesis, pyruvate metabolism, TCA cycle, and oxidative phosphorylation, and that these differentially expressed genes were not involved in amino acid metabolism. Gene expression analysis showed that the relative expression levels of MP synthesis genes (MpPKS5, MppA, MpFasB, MppB, MppD, and MppR2) were significantly up-regulated under acetic acid conditions. This study clarified the metabolic mechanism of acetic acid promoting the growth of M. ruber and the synthesis of MPs, which provided some theoretical guidance for the large-scale production of MPs in the industry in future.